Genetics of Stay-Green Trait and Its Association with Leaf Spot Tolerance and Pod Yield in Groundnut - Rukiya Danful; Yussif Baba Kassim; Doris Kanvenaa Puozaa; Richard Oteng-Frimpong; Masawudu Abdul Rasheed; Alexander Wireko-Kena; Richard Akromah (International Journal of Agronomy)
Despite its importance in providing income and food for smallholder farmers, fodder for livestock, and improving soil fertility through biological nitrogen fixation, groundnut yields are lowest on farmers’ fields in Sub-Saharan Africa due to biotic and abiotic constraints. Foliar fungal diseases account for over 80% reduction in groundnut productivity in some parts of Ghana. Unfortunately, chemical control of these foliar diseases has not yielded the desired results. Meanwhile, advances in phenotyping for disease tolerance in other crops have established a strong relationship between stay-green trait and foliar disease tolerance. However, this relationship has not been explored in groundnut. This study was designed to determine the genetic control of the stay-green trait and its relationship with leaf spot disease severity in groundnut. Twenty-five advanced groundnut breeding lines with varying degrees of tolerance for leaf spot tolerance were evaluated under diseased and disease-free conditions, after which four were selected for genetic studies. Results showed significant (p<0.001) differences among the genotypes for early leaf spot (ELS), late leaf spot (LLS), leaf area under greenness (LAUG), SPAD chlorophyll meter readings (SCMR), and yield traits. Leaf spot diseases caused 4.95 t·ha−1 (64.54%) pod yield reduction in CHINESE, the widely cultivated groundnut variety in Ghana. There was a strong correlation between LAUG and ELS (r = 0.82, p<0.001) and LLS (r = 0.63, p<0.001), and genotypes that were stay-green had tolerance to both diseases. Stay-green trait in groundnut was detected to be under the control of a single recessive gene and hence may be used to select for ELS and LLS resistance.